1985
DOI: 10.2527/jas1985.6061412x
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value of Normal and High Lysine Corns for Weanling and Growing-Finishing Swine when Fed at Four Lysine Levels

Abstract: SummaryOne-hundred-ninety-two weanling pigs from two separate trials, (initial weight 6.0 and 5.6 kg) and 400 growing-finishing pigs (initial weight 17 kg) were fed normal and high lysine corn diets containing four levels of lysine in a 2 • 4 factorial arrangement. Crossbred (Large White • Landrace x Duroc) pigs were used in all experiments. The objectives of the experiments were to (1) compare normal and high lysine corn when fed at different lysine levels, (2) determine the lysine requirements for the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…La quasi totalité de cette production nationale est constituée par des variétés de maïs ordinaire, majoritairement à grains jaunes. Cependant, ces variétés sont pauvres en protéines (9 à 10 %), et déficitaires en deux acides aminés essentiels, à savoir la lysine (0,23 %) et le tryptophane (0,06 %) (Beeson et al, 1966 ;Asche et al, 1985). L'utilisation de variétés de maïs ordinaire en alimentation sans suppléments peut entraîner des déficiences en vitamines et en acides aminés chez les populations.…”
Section: Introductionunclassified
“…La quasi totalité de cette production nationale est constituée par des variétés de maïs ordinaire, majoritairement à grains jaunes. Cependant, ces variétés sont pauvres en protéines (9 à 10 %), et déficitaires en deux acides aminés essentiels, à savoir la lysine (0,23 %) et le tryptophane (0,06 %) (Beeson et al, 1966 ;Asche et al, 1985). L'utilisation de variétés de maïs ordinaire en alimentation sans suppléments peut entraîner des déficiences en vitamines et en acides aminés chez les populations.…”
Section: Introductionunclassified
“…High‐lysine maize with homozygous embryo and endosperm for mutant alleles o 2 at the α‐zeins regulatory gene opaque‐2 shows about 60 to 100% increase in lysine and tryptophan and a higher BV (80% as compared with casein). Substituting normal maize with high‐lysine maize on an equal‐weight basis for growing pigs and sows can diminish the use of synthetic lysine in animal feeds to maintain proper amino acid balance (Asche et al, 1985; Burgoon et al, 1992; Knabe et al, 1992). In the USA, doubling lysine content in maize alone can add an estimated annual gross value of $360 million per year and can go up to $480 million per year if protein also is increased (Johnson et al, 2001).…”
mentioning
confidence: 99%
“…The results of a trial performed on pigs by Pinter et al (1995) demonstrated that N-retention of high-lysine maize was higher and it was possible to reduce the soyabean meal content in a ration by 27%. No significant influence of high-lysine maize used in grower and finisher diets for pigs instead of normal maize was found by Asche et al (1985).…”
Section: Discussionmentioning
confidence: 99%